Does the availability of single cigarettes promote or inhibit cigarette consumption? Perceptions, prevalence and correlates of single cigarette use among adult Mexican smokers. Issue 6 (10th August 2009) - Thrasher, J F; Villalobos, V; Dorantes-Alonso, A; Arillo-Santillán, E; Cummings, K Michael; O'Connor, R; Fong, G T
Abstract : Background: Single cigarette use and its implications have rarely been studied among adults. Objective: To assess perceptions, prevalence and correlates of single cigarette purchase behaviour and its relation to harm reduction. Design: Focus group transcripts and cross-sectional data were analysed. Setting and participants: Focus groups among convenience samples of adult smokers in two Mexican cities and a population-based sample of 1079 adult smokers from the International Tobacco Control Policy Evaluation Project in four Mexican cities. Main outcome measures: Purchase of single cigarettes last time cigarettes were bought, frequency of purchasing single cigarettes in the previous month and intention to quit in the next 6 months. Results: Focus group data indicated that smokers bought single cigarettes as a harm reduction strategy. Survey data indicated that 38% of participants purchased single cigarettes in the last month and 10% purchased them the last time they bought cigarettes, with more frequent consumption among young adults and those with lower income. Purchasing single cigarettes was independently associated with the frequency of using single cigarettes to reduce consumption and, less consistently, with the frequency of being cued to smoke after seeing single cigarettes for sale. Using single cigarettes to reduce consumption was positively associated with quit intention, whereas being cued to smoke by single cigarettes was negatively associated with quit intention. Conclusions: Study results suggest that some adult Mexican smokers purchase single cigarettes as a method to limit, cut down on and even quit smoking. Nevertheless, promotion of the availability of single cigarettes as a harm reduction strategy could provide additional smoking cues that undermine quit attempts and promote youth smoking.